A Scotsman's Odyssey - Macpherson, Ian G. (Conrad Press, The, 2020)
'A Scotsman's Odyssey' is a riveting account of four decades of sea adventures and exploration, written so vividly you can feel the salt spray in your face.Ian's maritime chronicle has something for everyone. His love of sailing has taken him to out-of-the-way places ranging from the sub-arctic Faroes Islands to the remote Barrier Reef islands in tropical Australia. 'A Scotsman's Odyssey' is a book as much about voyaging in the imagination as on the waves. It inspires cruising yachtsmen and yachtswomen to sail beyond their native shores, young readers to seize opportunities to sail on Ocean Youth Trust voyages, armchair sailors to journey to northern Europe and ancient Venetian ports in Greece and Croatia. Nature lovers will enjoy Ian's encounters with basking sharks, dolphins, killer and humpbacked whales, and even salt-water crocodiles